Economical Context of WorkRelated Stress - Kulvinskienė, Violeta Raimonda; Bandzienė, Agnė (Ekonomika, 2008)
Workrelated stress has a negative impact on business as well as on employees’ physical and psychological health. Economical costs for a company, caused by stress, are emplyees’ turnover, sickleaves, reduced productivity, increased accidents rate and lack of innovations. The object of the present n:search was workrelated stress. The aim of the research was to evaluate the work related stress level at Lithuanian automation and electrotechnical companies, to ekucidate workrelated stress outcomes, to evaluate the efficiency of stress interventions used by Lithuanian companies. The research was done in three stages. The work related stress level was measured in the first stage by using the HSE Management Standards Stress Model (sample of270 employees). According to the results, the role ambiguity causes the biggest stress and work control has the smallest impact on employees’ wellbeing. Analysis of workrelated stress among socio-demographic groups showed that different stressors affect men and women, but the general stress level is similar for both genders. The youngest employees undergo the biggest stress, while older employees are less stressed. Blue collar employees are more stressed at work compare to white collars. There is a positive correlation between stress level and management level, but there is no correlation between workrelated stress level and employees’ education. Longer service causes a higher stress level until a fixed stage, and later the workrelated stress level remains the same. Analysis of workrelated stress outcomes done in the second research stage showed a strong negative correlation between workrelated stress level and sickleaves. A higher workrelated stress level causes a bigger employees’ turnover, but no clear correlation was found. The aim of the third stage of the research was to find out managers’ view on stress, their beliefs about stress interventions by using the P. Dewe and M. O’Driscoll questionnaire (a sample of 34 managers). The five strategies most commonly reported as being used in organizations were those that could be described as the best practice of human resource techniques. They were communication and information sharing, clear goal and role descriptions, performance evaluation and feedback, social support and job autonomy. Stress interventions were evaluated mainly as average effective. These results show, that organizations have chosen right strategies, just they have to use them more effectively and start implementing not so widely used strategies, such as stress management training, management style changes, EAP. To reduce workrelated stress, for Lithuanian organizations it is recommended to create workrelated stress management policy and procedures, to improve communication, to define clear goals and roles, to organize stress management training for managers, periodically survey employees’ opinion.